Contribution of walking to and from school on overall physical activity: a one-year follow up study - Kensaku Sasayama (PLoS ONE, 2025)
This study is the first in Japan to prospectively examine the relationship between walking to and from school and physical activity in primary school children. A total of 76 participants completed baseline and follow-up assessments, and their mean age was 9.6 ±  1.0 years at baseline and 10.6 ±  1.0 years at follow-up. The participants’ mode of school commute was measured by a questionnaire. Step counts, sedentary time, light physical activity (LPA) and moderate-to-vigorous physical activity (MVPA) was assessed using an accelerometer. Comparisons of physical activity variables at baseline and follow-up and tracking of physical activity were analyzed. Overall physical activity levels decreased at follow-up compared to baseline. However, the contribution of commuting school activities to overall physical activity significantly increased at follow-up compared to baseline, especially in step counts and MVPA. Walking to and from school contributed to the participants’ overall physical activity in MVPA were 39.6 ±  15.3% and 49.1 ±  13.8% for all participants at baseline and follow-up, respectively. Tracking correlation coefficients were high for the steps counts (r =  0.80–0.89) and MVPA (r =  0.71–0.75) in commuting school. In conclusions, walking to and from school significantly contributed to overall physical activity in primary school students. Physical activity during the school commute in short-term exhibited a low-to-strong association. These findings emphasize the importance of promoting physical activity interventions and implementing school policies that encourage walking to and from school. Future research will need to examine other populations and countries over a long-term period.